2015
DOI: 10.2139/ssrn.2579926
|View full text |Cite
|
Sign up to set email alerts
|

Context-Dependent Cheating: Experimental Evidence from 16 Countries

Abstract: a b s t r a c tPolicy makers use several international indices that characterize countries according to the quality of their institutions. However, no effort has been made to study how the honesty of citizens varies across countries. This paper explores the honesty among citizens across 16 countries with 1440 participants. We employ a very simple task where participants face a trade-off between the joy of eating a fine chocolate and the disutility of having a threatened self-concept because of lying. Despite t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 31 publications
2
23
1
2
Order By: Relevance
“…The study of dishonest behavior has been the focus of a thriving research field for the last two or three decades. The fact that many people engage in dishonesty is well documented in this literature, although typically people do not cheat at the maximum possible level (Gneezy, 2005;Mazar et al, 2008;Fischbacher and Föllmi-Heusi, 2013;Fosgaard et al, 2013;Pascual-Ezama et al, 2015;Abeler et al, 2016;Jacobsen et al, 2017).…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…The study of dishonest behavior has been the focus of a thriving research field for the last two or three decades. The fact that many people engage in dishonesty is well documented in this literature, although typically people do not cheat at the maximum possible level (Gneezy, 2005;Mazar et al, 2008;Fischbacher and Föllmi-Heusi, 2013;Fosgaard et al, 2013;Pascual-Ezama et al, 2015;Abeler et al, 2016;Jacobsen et al, 2017).…”
Section: Introductionmentioning
confidence: 89%
“…A clear conjecture from the existing literature concerning dishonesty is that cheating will occur, but at relatively low levels (Mazar et al, 2008;Fischbacher and Föllmi-Heusi, 2013;Pascual-Ezama et al, 2015). Therefore, I expect that participants will overclaim their earnings, but will not systematically claim the maximum level.…”
Section: Cheatingmentioning
confidence: 97%
“…2013). Most studies investigate individuals from one single country (Allmon et al 2000), such as, Canada (Widelman 2009), China (Ma et al 2013), Hungary (Orosz et al 2013, Japan (Kobayashi and Fukushima 2012), South Korea (Park et al 2013), UK (Kirland 2009), and the US (Gino and Wiltermuth 2014;Premeaux 2010), with some exceptions (Pascual-Ezama et al 2015;Salter et al 2001;Tang et al 2011Tang et al , 2015. In this study, we incorporate social bonding theory.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Further, emotional cues and situational contexts play important roles in individuals' cheating and dishonesty across global economic pyramid Pascual-Ezama et al 2015;Tang et al 2011Tang et al , 2015. Based on 6382 managers in 31 geopolitical entities across six continents, results suggest that managers in good barrels (high CEV-Corporate Ethical Values/high CPI-Corruption Perceptions Index), mixed barrels (low CEV/high CPI or high CEV/low CPI), and bad barrels (low CEV/low CPI) exhibit low, medium, and high magnitude of dishonesty, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Since many studies (Pascual-Ezama et al, 2015) concluded that individuals tend to cheat more in the absence of external monitoring, then tightening laws and legislations against corruption is essential to compact it. Usually a person tends to trade-off the benefits from corrupt behaviour against the penalties if caught and punished.…”
Section: The Legislation Approach: Increase the Risk Of Corrupt Actsmentioning
confidence: 99%